Chemical homogeneity, microstructure and magnetic properties of LiTiZn ferrite ceramics doped with Al2O3 or ZrO2; Journal of Alloys and Compounds; Vol. 911 - Malyshev A. V. Andrei Vladimirovich (2022, 2022)
Title screen